Il problema dell’identità nel pensiero di Alfred Schütz - Sacchetti, Francesca (SocietàMutamentoPolitica, 2013)
The fundamental issue that motivates reflection of Alfred Schütz on the problem of identity is related to the way in which the subject can simultaneously have experience of himself both as multifaceted subject and as subject that owns a clear and strong awareness of his own existential unity. How can the subject escape the ‘vertigo’ that the transition from one region of sense to another, as well as the bringing into play of several layers of his personality, brings with it? How to live his versatility as a resource, and not as a limit? It is because of working that the subject is able to perceive himself as one and many at the same time. The self appears as a total self to the extent that, thanks the ‘doing’, is able to recompose the multifaceted complexity of its existence, and does so against the backdrop of a social dimension that is experienced as constituting one’s own being.